Bystander Effects and Profibrotic Interactions in Hepatic Stellate Cells during HIV and HCV Coinfection - Cintia Cevallos; Patricio Jarmoluk; Franco Sviercz; Cinthya A. M. López; Rosa N. Freiberger; M. Victoria Delpino; Jorge Quarleri (Journal of Immunology Research, 2024)
This study aims to explore the influence of coinfection with HCV and HIV on hepatic fibrosis. A coculture system was set up to actively replicate both viruses, incorporating CD4 T lymphocytes (Jurkat), hepatic stellate cells (LX-2), and hepatocytes (Huh7.5). LX-2 cells’ susceptibility to HIV infection was assessed through measurements of HIV receptor expression, exposure to cell-free virus, and cell-to-cell contact with HIV-infected Jurkat cells. The study evaluated profibrotic parameters, including programed cell death, ROS imbalance, cytokines (IL-6, TGF-β, and TNF-α), and extracellular matrix components (collagen, α-SMA, and MMP-9). The impact of HCV infection on LX-2/HIV-Jurkat was examined using soluble factors released from HCV-infected hepatocytes. Despite LX-2 cells being nonsusceptible to direct HIV infection, bystander effects were observed, leading to increased oxidative stress and dysregulated profibrotic cytokine release. Coculture with HIV-infected Jurkat cells intensified hepatic fibrosis, redox imbalance, expression of profibrotic cytokines, and extracellular matrix production. Conversely, HCV-infected Huh7.5 cells exhibited elevated profibrotic gene transcriptions but without measurable effects on the LX-2/HIV-Jurkat coculture. This study highlights how HIV-infected lymphocytes worsen hepatic fibrosis during HCV/HIV coinfection. They increase oxidative stress, profibrotic cytokine levels, and extracellular matrix production in hepatic stellate cells through direct contact and soluble factors. These insights offer valuable potential therapies for coinfected individuals.